IDENTIFIKASI FAKTOR YANG MEMPENGARUHI KINERJA UMKM - Mona Permatasari Mokodompit; Syarifuddin Syarifuddin; Sutiana Mutia (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This study aims to examine the influence of internal and external factors partially on the performance of Micro, Small, and Medium Enterprises (MSMEs) of the industrial sector in the Manokwari Regency. Research data is obtained by giving questionnaires and interviews with 34 MSMEs owners of the industrial sector in the Manokwari Regency. The data was then analyzed using a multiple linear regression analysis tools. The results of this study indicate that internal factors have no significant influence on the performance of MSMEs. Whereas, external factors have a significant influence on the performance of MSMEs.